“It’s not safe for me and what would it achieve?” Acceptability of patient-referral partner notification for sexually transmitted infections to young people, a mixed methods study from Zimbabwe - Joni Lariat; Chido Dziva Chikwari; Ethel Dauya; Valentine T. Baumu; Victor Kaisi; Laura Kafata; Esnath Meza; Victoria Simms; Constance Mackworth-Young; Helena Rochford; Anna Machiha; Tsitsi Bandason; et al. (Sexual and Reproductive Health Matters)
Partner notification (PN) is considered integral to the management of sexually transmitted infections (STI). Patient-referral is a common PN strategy and relies on index cases notifying and encouraging their partners to access treatment; however, it has shown limited efficacy. We conducted a mixed methods study to understand young people’s experiences of PN, particularly the risks and challenges encountered during patient-referral. All young people (16–24 years) attending a community-based sexual and reproductive health service in Zimbabwe who were diagnosed with an STI were counselled and offered PN slips, which enabled their partners to access free treatment at the service. PN slip uptake and partner treatment were recorded. Among 1807 young people (85.0% female) offered PN slips, 745 (41.2%) took up ≥1 PN slip and 103 partners (5.7%) returned for treatment. Most participants described feeling ill-equipped to counsel and persuade their partners to seek treatment. Between June and August 2021, youth researchers conducted in-depth interviews with 41 purposively selected young people diagnosed with an STI to explore their experiences of PN. PN posed considerable social risks, threatening their emotional and physical safety. Except for a minority in long-term, publicly acknowledged relationships, participants did not expect PN would achieve successful outcomes. Public health discourse, which constructs PN as “the right thing to do”, influenced participants to adopt narratives that concealed the difficulties of PN and their unmet needs. Urgent interrogation is needed of whether PN is a suitable or constructive strategy to continue pursuing with young people. To improve the outcomes of preventing reinfection and onward transmission of STIs, we must consider developing alternative strategies that better align with young people’s lived experiences.Plain language summary Partner notification is a public health strategy used to trace the sexual partners of people who have received a sexually transmitted infection (STI) diagnosis. It aims to interrupt the chains of STI transmission and prevent reinfection by treating both the person diagnosed and their sexual partners. The least effective but most common partner notification strategy used in many resource-limited settings is called “patient referral”. This involves a sexual healthcare provider encouraging the person diagnosed to give a “partner notification slip” to their potentially exposed sexual partner/s and persuading them to access treatment. This research sought to better understand young people’s experiences of partner notification, particularly the risks and challenges they faced during patient-referral.All young people (16–24 years) attending a community-based sexual and reproductive health service in Zimbabwe who were diagnosed with an STI were counselled and offered PN slips, which enabled their partners to access free treatment at the service. Young people trained as researchers interviewed 41 young people who had received a STI diagnosis to explore their experiences of partner notification.Only a small number (5.7%) of the partners of those who took a slip attended the service for treatment. Most participants felt they did not have the preparation, skills, or resources to persuade their partners to seek treatment. Many described negative experiences during and after partner notification, including relationship breakdown, reputation damage, and physical violence.These findings suggest that we should reconsider if partner notification is suitable or effective for use with young people. We should explore alternative approaches that do not present risks to young people’s social, emotional, and physical safety and well-being.